An over view about Maulana Abdul Haqq’s educational, social and political contributions: مولانا عبدالحق ؒکی علمی،سماجی اور سیاسی خدمات کاتحقیقی جائزہ - Jaan, Syed Hidayat Ullah; Ullah, Haris; Jaan, Syed Latif Ullah (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Maulana Abd-ul-Haqq was a great and famous Islamic scholar, basically his family was migrated from Afghanistan centuries ago and settled in Akora Khattak (Khyber PakhtunKhwah, Pakistan). He was belonged to a religious family, His father was also a religious scholar. He received his primary education at home and at last visited university of “Darul Uloom Deoband India” for higher education, late after he founded “Darul Uloom Haqqania Akora Khattak, Kp, pakistan” which is one of the best Islamic teaching university among the world, He not only contribute in the education field only but also play a well-known role in the social affairs and in the national politics as well that’s why He reformed various traditions of marriage and grief. He fully opposed the Ahmadiyya’s movement on the floor of the assembly. Here we get an over view about is educational, social and political contributions that shows various fruitful dimensions about his life.